Are tax exemptions for electric cars an efficient climate policy measure? - Geir H. Bjertnæs (Statistics Norway, Research Department, 2013)
This study finds that the welfare gain, excluding environmental effects, generated by increasing the Norwegian tax rate on purchase of electric cars from 8 to 37 percent amounts to approximately 5500- 6500 NOK (or 680-820 euro) per ton increase in GHG emissions in the long run. Substantial tax exemptions implies that reallocation from electric cars towards petrol and diesel powered cars generates a tax revenue gain of more than 40 billion NOK, which amounts to almost 10 percent of government consumption in 2007.
Keywords: Q54; R48; H23; 330; Taxation; Electric cars; CO2 emissions